2017
DOI: 10.1002/cbf.3279
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular NAMPT/visfatin causes p53 deacetylation via NAD production and SIRT1 activation in breast cancer cells

Abstract: Visfatin, which is secreted as an adipokine and cytokine, has been implicated in cancer development and progression. In this study, we investigated the NAD-producing ability of visfatin and its relationship with SIRT1 (silent information regulator 2) and p53 to clarify the role of visfatin in breast cancer. MCF-7 breast cancer cells were cultured and treated with visfatin. SIRT1 activity was assessed by measuring fluorescence intensity from fluoro-substrate peptide. To investigate the effect of visfatin on p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…In melanoma cells, NAMPT regulation of the E2F family member 2 was shown to impact transcription and translation of SIRT1, and genetic or pharmacologic loss of NAMPT activity resulted in activation of TP53 and apoptotic cell death (79). A similar regulatory network has been described in breast cancer cells where increased SIRT1 activity and induction of deacetylation of TP53 were observed upon exposure to the extracellular form of NAMPT (80).…”
Section: Sirtuin Functionmentioning
confidence: 72%
“…In melanoma cells, NAMPT regulation of the E2F family member 2 was shown to impact transcription and translation of SIRT1, and genetic or pharmacologic loss of NAMPT activity resulted in activation of TP53 and apoptotic cell death (79). A similar regulatory network has been described in breast cancer cells where increased SIRT1 activity and induction of deacetylation of TP53 were observed upon exposure to the extracellular form of NAMPT (80).…”
Section: Sirtuin Functionmentioning
confidence: 72%
“…Numerous previous studies on established cell lines have shown that eNampt exerts a stimulating effect on the rate of proliferation of different cancer cells. Such action has been observed, inter alia, in the case of MCF-7 and MDA-MB-231 breast cancer cells [23,24], PC3 prostate cancer cell [25] Me45 melanoma cell [18], hepatocellular carcinoma (HCC) cells [26], AGS gastric cancer cell line [27] Ishikawa and KLE endometrial carcinoma cell lines [28]. No Nampt receptor has been identified so far and the stimulating effect of Nampt on proliferation most probably occurs through AKT/PI3K, ERK/ MAPK and GSK-3β proteins signaling pathways [23,25,26,28].…”
Section: Discussionmentioning
confidence: 81%
“…As known, Nampt plays a central role in the systemic regulation of NAD biosynthesis in cells, hence it can also regulate their proliferation. In the available literature there are many publications that this cytokine exerts dose-dependent stimulating effect on proliferative activity, mainly of cancer cells [18,[23][24][25][26][27][28]. This stimulation occurred probably through AKT/PI3K, ERK/MAPK and GSK-3β proteins [23,25,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…Visfatin increases both extracellular and intracellular nicotinamide adenine dinucleotide (NAD) concentration in breast cancer cells, which causes upregulation of silent information regulator 1 (SIRT1) activity and p53 deacetylation. SIRT1 is implicated in blocking senescence and apoptosis and promoting cancer growth ( 127 ).…”
Section: Bmas and Mechanisms Responsible For Macrometastasis And Outgmentioning
confidence: 99%